Development of Fruits Adventure Circuit Game to Stimulate Gross Motor Skills of Early Childhood Children - Aqila, Dhinie Zharwa Nur; Pramono, Pramono; Tirtaningsih, Munaisra Tri (Universitas Negeri Malang, 2024)
The purpose of this research is to create the educational game ‘Circuit Fruits Adventure,’ which is intended to help children in the age range of five to six years improve their gross motor skills. The game is an adaptation of Circuit Mini Jungle, which emphasises on improving motor skills, such as balance, coordination, strength, and agility. The research and development (R&D) methodology used in this study includes the following stages: needs analysis, product design, model development, expert validation, and small group and large group trials. The development process began with the identification of the needs of teachersand students at Ta Asri Islamic Kindergarten Malang City and Al-Hidayah Gogodeso 1 Kindergarten Blitar Regency, accompanied by empirical and theoretical studies. After being collected through interviews, questionnaires, and recording, the data were then analysed qualitatively and quantitatively. The product was validated by game experts and motor experts, and tested on 8 children in a small group and 21 children in a large group to evaluate the effectiveness, efficiency, and attractiveness of the product. As a result, children aged between five and six years old can improve their gross motor skills by playing the game ‘Circuit Fruits Adventure.’ Validation tests by game experts and motor experts showed that the game is highly valid, effective, efficient, and attractive. As a result, it is expected that this game can significantly advance early childhood education. Keywords: Circuit Games, Gross Motor, Early Childhood